Recent Concepts for Supramolecular 2D Materials - Gallego, Lucía; Woods, Joseph F.; Rickhaus, Michel (Organic Materials, 2022)
Bottom-up approaches are one strategy geared towards designing novel two-dimensional materials. Supramolecular polymerization has proven to be an effective way of obtaining these architectures due to the increasing control and tunability offered by different functional groups, which are not afforded by conventional polymerization. In this short review, we highlight examples of supramolecular assemblies held together by well-known non-covalent interactions, as well as new approaches that are becoming more relevant in recent years.
Keywords: two-dimensional materials; supramolecular polymers; hydrogen bonding; π–π interactions; hydrophobicity; curvature